2012
DOI: 10.1590/s1517-83822012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Alkali pretreated of wheat straw and its enzymatic hydrolysis

Abstract: The efficiency of enzymatic hydrolysis of cellulose can be improved by various pretreatments of the substrate. In order to increase the efficiency of enzymatic saccharification of the wheat straw, we determined the effect of different pretreatments on the physical structure, chemical components and enzymatic saccharification of wheat straw. Our results showed that combination of grinding and sodium hydroxide (NaOH) treatment had high effect on the enzymatic hydrolysis of wheat straws. The optimal pretreatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
37
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(51 citation statements)
references
References 27 publications
10
37
0
4
Order By: Relevance
“…There is no current record of work done on the effect of substrate concentration on the rate of enzymatic pretreatment of biomass. Similar works on enzymatic saccharification of biomass reported by Han et al (2012) showed that enzyme reactions are retarded when the concentration of substrate for an enzyme medium is exceeded, leading to a reduction in the product and accumulation of the substrate. Total sugar (mg/ml) % weight loss…”
Section: Effect Of Substrate Concentration On the Enzymatic Pretreatmsupporting
confidence: 65%
“…There is no current record of work done on the effect of substrate concentration on the rate of enzymatic pretreatment of biomass. Similar works on enzymatic saccharification of biomass reported by Han et al (2012) showed that enzyme reactions are retarded when the concentration of substrate for an enzyme medium is exceeded, leading to a reduction in the product and accumulation of the substrate. Total sugar (mg/ml) % weight loss…”
Section: Effect Of Substrate Concentration On the Enzymatic Pretreatmsupporting
confidence: 65%
“…The problem could be addressed by using a yeast growth medium, which would enhance the viability of yeast cells and increase ethanol yield per g of wheat straw. 50 , the effi ciency of enzymatic hydrolysis of cellulosic biomass can be increased by grinding and pretreating raw material under alkaline conditions. In the cited studies, the effi ciency of enzymatic hydrolysis increased with a rise in NaOH concentrations, and the highest content of reducing sugars was noted at 1% NaOH.…”
Section: Resultsmentioning
confidence: 99%
“…Appropriately, increasing alkaline concentration was conducive to the dissolution of hemicellulose and low polymerization of cellulose, and also to the swelling of cellulose (Wu et al 2010). However, using an excessive dosage of NaOH and Na2S could cause a serious degradation of the raw materials (Han et al 2012). The dissolution rate of C-5 was significantly higher than that of C-1.…”
Section: Naoh and Na2s Combined Pretreatmentmentioning
confidence: 97%